Responsiveness of the order fulfilment process - Kritchanchai, Duangpun; MacCarthy, B.L. (Emerald, 1999)
This paper discusses evidence from field studies undertaken to investigate the responsiveness of the order fulfilment process in a number of companies. The evidence is analysed in the context of the literature on responsiveness and related areas such as time-based competition. Similarities and differences are analysed across a number of industrial sectors with respect to order fulfilment processes and the interpretation and significance of responsiveness. Generic factors that influence different types of companies are identified. Four components of responsiveness - stimuli, awareness, capabilities and goals - emerge from an analysis of the literature. The field and case study evidence allows the development of more precise definitions and descriptions of each of these components. The study also allows a generic responsiveness framework to be developed that incorporates both strategic and operational viewpoints. The need for more field studies on responsiveness is noted. More work is advocated on the assessment and measurement of responsiveness and on developing appropriate responsiveness interventions, particularly with respect to the order fulfilment process.